Postmodernism and Political Correctness: The Decline of Reason and Free Speech - BOUDERBALA, Abdelhak; BOUMOUS ,Moufida (Faculty of Letters and Foreign Languages Department of English, 2019)
During the past few decades, a controversial topic has been roaming mainly in the radar of the Western civilization. New political parties and new philosophies rose with ground-breaking ideas and demands for change in the political and social systems. Since the 1980’s, the issues of political correctness and the postmodern activism have been triggering endless debates and discussions, as the Western world grew polarized. This topic has been an intense source for authors, philosophers, and journalists across Europe and the United States. Several books, articles, and debates have been produced to discuss this issue alone until this day. And while it is a widely known concept among intellectuals, the majority of people have yet to put their hands on its exact meaning, its real purpose, and its consequences. This study aims to provide the simplest possible definition for political correctness, to explore its history and context within the postmodernist thinking, and to clarify its effects on today’s society, politics, and free speech